Carrera de Turismo Realizó recorrido por los predios de la UEB - García García, Mariana (2023)
The students of the eighth cycle of the Tourism and Hospitality career, in the company of their teachers, carried out the second pilot test of the academic tourist route “My UEB”, the tour began at the Dr. Gabriel Galarza López campus matrix, Later they had the opportunity to listen to the UEB cultural group, who delighted them with some musical pieces at the CENI.